Study on Sedimentary Environment Elements and Sedimentary Model of Lacustrine Shale in E1f2 Member, Gaoyou Depression, Subei Basin - Ma, Cunfei; Huang, Wenjun; Zou, Kaizhen; Ma, Xiaonan; Liu, Zhenyang; Yin, He; Liu, Shili (Frontiers in Earth Science, 2022)
Lacustrine shale is rich in hydrocarbon resources, but with complex lithology, strong heterogeneity and it is also controlled obviously by sedimentary environment. By integrating cores, thin section, X-ray diffraction analysis, trace elements, organic geochemical indexes and paleontological data, this paper studies sedimentary environment elements and sedimentary model of shale in E1f2 member, Gaoyou Depression, Subei Basin. Shale in E1f2 Member is totally shore lacustrine deposits forming under dry hot climate of central and south Asia tropical. Lake basin extended continuously, with brackish water, strong reduction and medium water stratification. Transgression resulted in water rapid rise, salinity, reducibility and water stratification increase. With climate changing wet later, the water decreased slightly, salinity, reducibility and water stratification also decreased. Shale in E1f2 member is characterized by sedimentary zones, which are divided into muddy water desalination deposit and clear water salinization deposit, including muddy water desalination deposit in flooded zone, clean water salinization deposit in transition zone and still water salinization deposit in clear water zone. Under palaeotopography settings of E1f2 member, combining characteristics of vertical stratification and plane zone of the lake, an integrated sedimentary model of lacustrine shale in flat platform has been established under climate and transgression control. The plane area of lake can be divided into slow slope zone, sub-depression zone, processes zone, deep slope zone and deep depression zone, which correspond roughly to the sedimentary zones of flooded zone, transition zone and clear water zone. The oil shale enriched in low-lying parts of paleotopography is mainly deposited in the end of muddy water area and clear water area.